Digital Governance Transformation and Agile Governance Outcomes in Public Services: A Case Study of Pakuan Prima in Bogor City - Nugraha, Diva; Sri Kartini, Dede; Kasman, Andi (Jurnal Studi Pemerintahan, 2025)
The government holds the responsibility of delivering public services that are effective, efficient, and adaptive to contemporary developments. The utilization of information and communication technology (ICT) has given rise to the practice of digital government. Bogor City is among the regions that have implemented digital service transformation through the Pakuan Prima platform, managed by the Department of Population and Civil Registration (Disdukcapil). This study aims to analyze the implementation of digital governance transformation through Pakuan Prima services and to examine the extent to which the principles of agile governance are reflected in its practice. A quantitative approach was employed using a survey method, involving 100 respondents drawn from a total population of 9,670 users. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings reveal that digital governance transformation through Pakuan Prima achieved an average score of 4.09 (categorized as good), the e-services variable scored 4.22 (very good), while the agile governance variable recorded 4.04 (good). Statistically, digital governance transformation has a significant effect on e-services, e-services significantly influence agile governance, and digital governance transformation indirectly impacts agile governance through e-services. These results underscore that the implementation of digital transformation enhances the quality of public services and supports a form of governance that is more agile, responsive, and citizen-oriented.